Tenancy Choice in a Competitive Framework with Transactions Costs - Alston, Lee J.; Datta, Samar K.; Nugent, Jeffrey B. (Journal of Political Economy, 1984)
The choice between wage labor and sharecrop contracts is analyzed in a model that avoids both the pitfalls of previous models–inefficiency of sharecropping and indeterminacy–by introducing transactions costs with appropriate nonlinearities. Plantation data from the American South provide empirical support for the hypothesized nonlinearity in transactions costs and simultaneous determination of direct supervision and contractual choice.